The Role of Positive Parenting Support in Developing Self-Leadership Among Grade XI Adolescents at Madrasah Aliyah Swasta Ubudiyah P. Brandan - Hasanah, Nurul; -, Susanti; Sitepu, Fatmawati; Hasyim , Laila (unprimdn.ac.id, 2025)
Self-leadership equips teenagers with self-awareness, responsibility, and motivation to navigate the transitions more effectively. These skills form a crucial foundation for self-reliance, future success, and the ability to make choices that align with their values and life goals. This study aims to determine the impact of positive parenting on teenage self-leadership. This study was conducted at the Ubudiyah P. Brandan Private Islamic High School. This research method uses a non-test technique in the form of a questionnaire. The sample of this study consisted of 65 XII students. The sampling technique was carried out using the Slovin formula, resulting in a total of 56 samples. This study uses a simple regression analysis to see how much impact Positive Parenting has on the Self-Leadership of Grade XI Adolescents at the Ubudiyah P. Brandan Private Islamic High School. The results of the study indicate that there are positive influences of parenting on self-leadership in students at Ubudiyah P. Brandan Binjai Private Islamic High School, with a significance test of P < 0.000 and the equation Y = 9.99 + 0.90X. Furthermore, based on the test results, the variable's influence is reflected in an R-Square value of 0.996 (99.6%). This data shows that there is a significant influence of self-compassion on resilience, with a 99.6% effect. At the same time, other factors influence 0.4%.